Identification of usability problems and requirements of elderly Chinese users for smart TV interactions. Issue 7 (3rd July 2019) - Dou, Jinhua; Qin, Jingyan; Wang, Qingju; Zhao, Qichao
ABSTRACT: With the development of Information and Communications Technology (ICT), smart TV is gradually becoming universal and penetrating daily life. Smart TV has a wide range of user groups, and the elderly is an important group. The special physiological and psychological characteristics of Chinese elderly highlight the usability problems of smart TV interactions for them. The main functions of smart TVs were selected and operated by the elderly in this study. With the help of physiological measurements, behaviour analyses and interviews during natural usage scenarios, we determined the usability issues and user requirements of Chinese elderly for interacting with smart TVs. The research shows that the elderly in China have the intention to use smart TV products, but the usability of interactive systems affects the experience of using a smart TV. The results indicate that different content search methods result in different user experiences. Pinyin search is difficult to operate using a remote control, and some influencing factors are revealed. Voice search results in the best user experience for the elderly, but the recognition accuracy is easily affected by factors such as user accents and environmental noise. Hierarchical search is easy to operate, but it often takes a long time to finish an involved task. Other usability issues of some main functions, i.e. screen mirroring, shopping, playing games, system settings and application downloads, were also obtained, and the requirements of the elderly were well understood. These findings have implications for interaction design and implementation of smart TV service systems.